Synthesis of new glycosylated flavonoids with inhibitory activity on cell growth - Neves A.R. (2018)
Natural flavonoids and xanthone glycosides display several biological activities, with the glycoside moiety playing an important role in the mechanism of action of these metabolites. Herein, to give further insights into the inhibitory activity on cell growth of these classes of compounds, the synthesis of four flavonoids (5, 6, 9, and 10) and one xanthone (7) containing one or more acetoglycoside moieties was carried out. Acetyl groups were introduced using acetic anhydride and microwave irradiation. The introduction of one or two acetoglycoside moieties in the framework of 3,7-dihydroxyflavone (4) was performed using two synthetic methods: the Michael reaction and the Koenigs-Knorr reaction. The in vitro cell growth inhibitory activity of compounds 5, 6, 7, 9, and 10 was investigated in six human tumor cell lines: A375-C5 (malignant melanoma IL-1 insensitive), MCF-7 (breast adenocarcinoma), NCI-H460 (non-small cell lung cancer), U251 (glioblastoma astrocytoma), U373 (glioblastoma astrocytoma), and U87MG (glioblastoma astrocytoma). The new flavonoid 3-hydroxy-7-(2,3,4,6-tetra-O-acetyl-β-glucopyranosyl) flavone (10) was the most potent compound in all tumor cell lines tested, with GI50 values < 8 µM and a notable degree of selectivity for cancer cells. © 2018 by the authors.